FIQIH SOSIAL : ANTARA FORMALISTIK FIQIH DAN TUJUAN FIQIH, UPAYA DALAM MEMBANGUN KARAKTER UMMAT - Rosita, Desyi; Masitoh, Imas; Aminudin, Aminudin; Nurazizah, Wafiq (Staisman Press, 2023)
Fiqh is often interpreted as a human effort, which involves a process of reasoning, both at the theoretical and practical levels, in understanding, describing and elaborating religious laws. By calling it humane it is intended to distinguish fiqh from sharia. The latter is loosely understood to refer to the Islamic religion or divine law as contained in the corpus of revelation without involving human hands. In other words, fiqh is a reflection of the Shari'a. Because fiqh grows from the results of istinbath (legal exploration), fatwa and ijtihad, certain tools are needed to regulate the achievement of fiqh products, known as ushul fiqh (legal theory) and qawa'id fiqhiyyah. Social fiqh is also very closely related to human benefit in the framework of maqashid sharia. The purpose of fiqh is not just an individual approach or relationship with Allah, but rather an individual relationship with the surrounding community to establish friendship and build a high sense of humanity and social life. Apart from that, cultivating that character is also the psychological characteristics of morals and manners. The formation of character in Islam can also be called akhlakul karimah, which is where one can control oneself from desires that are positive or vice versa. The purpose of fiqh itself in life is to make Islam khaffah (perfect), as well as a guide in everyday life.